Garra longchuanensis, a new cyprinid (Teleostei: Cypriniformes) from southern China - Yu, Qian; Wang, Xuzheng; Xiong, Huan; He, Shunping (Zootaxa, 2016)
A new species of the genus Garra is described from the Longchuan Jiang River, a tributary flowing to the Yiluowadi Jiang (Irrawaddy River) basin in Tengchong, Yunnan, South China. Garra longchuanensis is distinct from other Chinese congeners, except for G. qiaojiensis, in having 12 circumpeduncular scales, a well-developed rostral lobe with irregular distributed acanthoid tubercles, a deep groove to form a transverse lobe and a conspicuous, heavily tuberculated quadrate proboscis, and from G. qiaojiensis in having a slightly pointed snout (vs. rounded), a long and slender caudal peduncle (length 17.8–20.6% SL vs. 15.5–17.1%, width 10.9–12.6% SL vs. 11.3–12.6%), pectoral fin with 15–16 (vs. 13) branched rays, pelvic fin with 9 (vs. 8) branched rays, and an anterior position of anus (anus to anal distance 27.2–39.1% of pelvic to anal distance vs. 22.8–28.3%).